Effects of adjustments to wheelchair seat to back support angle on head, neck, and shoulder postures in subjects with cerebral palsy. Issue 6 (2nd November 2021) - Alkhateeb, Afnan M.; Daher, Noha S.; Forrester, Bonnie J.; Martin, Bradford D.; Jaber, Hatem M.
ABSTRACT: A wheelchair is usually a source of mobility for people with moderate to severe cerebral palsy, who are unable to walk. They spend long periods of time sitting in their wheelchair, which can affect their head and neck alignment. Opening the seat to back support angle of the wheelchair can modify realignment of body segments and improve posture. Aims : To examine the effect of seat to back support angle adjustments on head, neck, and shoulder postural alignment in people with cerebral palsy. Methods : Nine participants with cerebral palsy who use a wheelchair for mobility sat in a research wheelchair. Sagittal head angle (SHA), cervical angle (CVA), and shoulder angle (SA) from photographs were examined using the Coach's Eye device during three different seat to back support angles of the wheelchair (90°, 100°, 110°). Results : There were significant differences in mean SHA and CVA among the different seat to back support angles ( p < .001). However, there was no significant difference in mean SA. Conclusion : Head (SHA) and (CVA) alignment was closest to neutral posture with seat to back support angles set at 110°. Thus, adjusting the wheelchair back support to a 110º would provide the most appropriate sagittal head and cervical angle for this population.